1994
DOI: 10.1038/sj.bdj.4808437
|View full text |Cite
|
Sign up to set email alerts
|

Sugar consumption and dental caries: evidence from 90 countries

Abstract: An examination is made of data on dental caries amongst 12-year-old children and sugar consumption of the total population for 90 countries. For the whole data set, DMFT score tends to rise with sugar consumption. The linear relationship between the logarithm of DMFT and sugar is estimated to have a slope of 0.021 per kg/year per head of population (P < 0.0001), and accounts for 28% of the variation in DMFT. In contrast, when data from 29 industrialised nations are analysed separately, there is no evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
2
8

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 0 publications
4
74
2
8
Order By: Relevance
“…O aumento do consumo de alimentos industrializados -em especial, açúcar e outros tipos de carboidratos fermentáveis -é tido como o principal fator envolvido na alteração do perfil de saúde bucal dessas populações. Há ampla literatura que indica a estreita e positiva relação entre consumo de açúcar e prevalência de cárie (Gustafsson et al, 1954;Newbrum, 1982;Pilot, 1988;Sheihan, 1984;Woodward & Walker, 1994).…”
Section: Discussionunclassified
“…O aumento do consumo de alimentos industrializados -em especial, açúcar e outros tipos de carboidratos fermentáveis -é tido como o principal fator envolvido na alteração do perfil de saúde bucal dessas populações. Há ampla literatura que indica a estreita e positiva relação entre consumo de açúcar e prevalência de cárie (Gustafsson et al, 1954;Newbrum, 1982;Pilot, 1988;Sheihan, 1984;Woodward & Walker, 1994).…”
Section: Discussionunclassified
“…To examine whether sugar reductions at a population level relate to lower caries in practice, changes in sugar supply were plotted against changes in caries experience in 67 countries using the Sreebny (1982) and Woodward & Walker (1994) data sets (Figure 3). The results show reductions in both sugar supply and caries in 18 countries (lower left quadrant of Figure 3) but in 25 countries there has been an increase in sugar supply combined with a reduction in caries experience (lower right quadrant of Figure 3).…”
Section: Guidelines For Sugar Consumption In Europe Chs Ruxton Et Almentioning
confidence: 99%
“…In a review of caries prevalence in relation to diet, Marthaler (1990) concluded`in those countries where caries prevalence is declining, the overall consumption of sugar is ceasing to be the most important Figure 2 National sugar supply vs dental caries in 12 y olds for 90 countries. Source: Woodward & Walker (1994); industrial r 7 0.09 NS: developing r 0.49, P`0.01.…”
Section: Guidelines For Sugar Consumption In Europe Chs Ruxton Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…More recently Woodward & Walker (1994) have published data on per capita sugars consumption in 12-year-old children from 90 countries. DMFT increased with sugars consumption, but the rate of increase was lower than that found by Sreebny (1982).…”
Section: Epidemiological Surveysmentioning
confidence: 99%